Balthasar Hubmaier (1480/85-1528) - Vincent, Jean-Marcel (Bulletin de la Société de l'Histoire du Protestantisme Français, 1978)
This paper offers an introduction to the history of Anabaptism between 1522 and 1527. It gives a survey of present anabaptist historiography (till 1973). The Study of Balthasar Hubmaier's life guides us in this period which is marked by the abundance of new theological ideas and of practical ecclesiological realizations. Hubmaier met, or at least read, the main figures of the official reformation. Moreover, his short theological writings help us to perceive the main themes of controversy among the "radical reformers" themselves.